(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The Tragic Sense of Life was one of Miguel de Unamuno’s great philosophical-religious contributions. It is true that next to his tragic conception of existence we find juxtaposed concepts as fundamental and decisive as those of conatus essendi, life struggle, faith and God, but, while admitting these, in the present study we address only the polemical and anguished relation that pistis has with gnosis, or in other words, that faith has with reason, in relation to the ultimate fate of individual consciences. Thus we attempt to highlight the most characteristic and symbolic traits of human existence as conceptualized by Unamuno at the turn of the 19th to the 20th century, when positivism and phenomenology seemed to challenge metaphysics as a legitimate branch of knowledge.